Governance and Quintuple Helix innovation model: Insights from the local government of East Luwu Regency, Indonesia - Abdillah, Abdillah; Widianingsih, Ida; Buchari, Rd Ahmad; Mustari, Nuryanti; Saleh, Syafiuddin (Frontiers in Climate, 2022)
The threat of climate change has a strong impact on the social and ecological systems of rural communities in East Luwu Regency, Indonesia. These impacts pose complex and varied challenges that can only be handled through a collaborative, sustainable and distributed innovation development process in every innovation sector for regional/regional resilience and independence. See, the theoretical framework of Collaborative Governance is often highly conceptual, with little focus on the actual governance mechanisms that facilitate it. This study examines the concept of rural living as an interaction design between organizations and the process of developing sustainable rural innovation. Where multi-stakeholder interactions form the Quintuple Helix innovation model through a multidimensional case study design, which focuses on the concept of innovation participation, knowledge production, innovation ecosystem as a social subsystem system, and socio-ecological transition towards the development of independent rural areas, sustainability of rural innovation programs, and disaster preparedness in East Luwu Regency. This research provides a deeper understanding of the rural innovation process to address socio-ecological challenges through the importance of government-public-private-university synergy and its context in Magani Village and Sorowako Village, East Luwu Regency. The strong innovation drive from the collaboration between the East Luwu Government and PT Vale Tbk is the key to the sustainability of rural innovation that encourages village innovation and village community participation in the village innovation process, so that it has an impact on village community independence, and environmental sustainability in East Luwu Regency. Although rural innovation in East Luwu Regency is still lacking in terms of communication and coordination between actors and sectors.